Is Qualitative Research in Education Being Lost in Spain? Analysis and Reflections on the Problems Arising from Generating Knowledge Hegemonically - Fernández-Navas, Manuel; Alcaraz-Salarirche, Noelia; Pérez-Granados, Laura; Postigo-Fuentes, Ana Yara (The Qualitative Report, 2020)
In this paper we reflect on how qualitative research in education in Spain has become invisible, by asking a series of questions. What are the effects of this? What are the keys to understand this marginalisation of qualitative research? What are the implications for researchers and students? What challenges does qualitative research face in order to overcome this lack of visibility? To discuss these issues, we present a series of structured reflections in the form of an essay based on the preliminary impressions that have emerged in the course of a broader investigation that we are conducting and that focuses on the state of qualitative research in education in Spain. Our intention is, on the one hand, to offer a vision of the Spanish panorama to the international community, and on the other hand, to transfer the ideas that have emerged during the course of the research that we are developing to serve as a reflection and resource to other qualitative researchers.
Keywords: Investigación cualitativa; Educación - Investigación; España - Investigación; Qualitative research; Policies; Paradigm Wars; Research training; Publications